CONFLICT MANAGEMENT STRATEGIES IN THE MULTICULTURAL CITY OF BUKIT BINTANG - Malfiyolla; Bayu Wijayanto; Dedi Hermon; Febriandi (RADJA PUBLIKA, 2026)
This study examines how conflict management strategies are implemented in the multicultural area of Bukit Bintang, Kuala Lumpur, Malaysia. This district is known as an economic and tourism hub that brings together people from diverse backgrounds every day, ranging from Malay, Chinese, and Indian communities to expatriates from around the world (Abdullah, 2019). Such diversity is a strength that makes Bukit Bintang vibrant, yet it can also give rise to tensions—socially, economically, and culturally. The history of Kuala Lumpur’s urbanization shows that multiethnic interactions have not always been smooth, particularly when related to resource distribution or the use of public spaces. To understand these conditions, the study employs a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The findings show that Bukit Bintang’s primary strength lies in its diversity, but weaknesses emerge due to limited regulations and the absence of dialogue spaces that can bring all parties together. On the other hand, increasing awareness of the importance of multiculturalism and supportive government policies create major opportunities for fostering harmony. However, threats such as social segregation and economic inequality continue to loom. The proposed strategies include strengthening cross-cultural forums, promoting cultural literacy education, and creating inclusive policies based on community participation. With these measures, Bukit Bintang has the potential to become a real example of how a multicultural city can grow peacefully and adaptively in the era of globalization.